Fatal Chromobacterium violaceum septicaemia in northern Laos, a modified oxidase test and post-mortem forensic family G6PD analysis - Mayxay Mayfong; Moore Catrin E; Sengduangphachanh Amphonesavanh; Vongsouvath Manivanh; Silisouk Joy; Inthalad Saythong; Douangdala Phouvieng; Slesak Günther; Matsuoka Hiroyuki; Newton Paul N (BMC, 2009)
Abstract Background Chromobacterium violaceum is a Gram negative facultative anaerobic bacillus, found in soil and stagnant water, that usually has a violet pigmented appearance on agar culture. It is rarely described as a human pathogen, mostly from tropical and subtropical areas. Case presentation A 53 year-old farmer died with Chromobacterium violaceum septicemia in Laos. A modified oxidase method was used to demonstrate that this violacious organism was oxidase positive. Forensic analysis of the glucose-6-phosphate dehydrogenase genotypes of his family suggest that the deceased patient did not have this possible predisposing condition. Conclusion C. violaceum infection should be included in the differential diagnosis in patients presenting with community-acquired septicaemia in tropical and subtropical areas. The apparently neglected but simple modified oxidase test may be useful in the oxidase assessment of other violet-pigmented organisms or of those growing on violet coloured agar.